Population genetic structure of pedunculate oak (Quercus robur L.) in Belarus according to the analysis of chloroplast DNA - Padutov, Vladimir E. (Experimental Biology and Biotechnology, 2021)
Pedunculate oak (Quercus robur L.) is one of the main forest forming species in the Republic of Belarus. Its population genetic structure was formed under the influence of various migration processes. Six chloroplast DNA loci (µdt1, µdt3, µdt4, µcd4, µcd5 and µkk4) were used for the genogeographic study. The material for the analysis was collected in 100 oak forest stands (2325 samples); 18 allelic variants were identified, which are grouped into 17 different combinations (haplotypes). Five of them are widespread (the proportion of occurrence varies from 7 to 48 %, totalling 85 %). The remaining 12 are rare (the proportion of occurrence varies from 1 to 3 %, totalling 15 %). Phylogenetic trees constructed using the nearest neighbour and maximum likelihood methods show the presence of two groups (branches) of haplotypes. One of it comprises 8 variants including 2 dominant haplotypes and the other comprises 9 variants including 3 dominant haplotypes. PCR-RFLP analysis of chloroplast DNA showed that the pedunculate oak in Belarus originates from the Balkan refugium. Haplotype No. 1 (µdt189, µdt3123, µdt4142, µcd494, µcd574, µkk4109) is found almost everywhere in Belarus with the exception of the southwest and northeast, while haplotype No. 8 (µdt189, µdt3121, µdt4142, µcd494, µcd574, µkk4109) is mainly localised in the southwest and northeast. Haplotypes No. 3 (µdt189, µdt3120, µdt4141, µcd494, µcd575, µkk4109) and No. 7 (µdt189, µdt3122, µdt4142, µcd494, µcd574, µkk4109) predominantly found in the west of the country. Haplotype No. 2 (µdt190, µdt3120, µdt4141, µcd495, µcd574, µkk4109) is typical for the southeast.